Entering the Arena: The Figured Worlds Transition of Preservice Teachers - Saunders, Jane M; Ash, Gwynne Ellen (Journal of adolescent & adult literacy, 2013)
The article describes a semester-long project that draws on Suzanne Collins' "The Hunger Games" as a resource and over-arching theme for preservice teachers taking a content area literacy course. We examine how preservice teachers learn to connect written texts to content area (disciplinary) literacy and consider ways to prepare them for the myriad hidden rules of teaching in today's complex public school environments. Included are examples from our students' work, as is a detailed description of our over-arching goals for The "Hunger Games" Achievements project. (Contains 5 figures and 3 resources.)